Strategic use of verbal and non-verbal cues in marketing by PepsiCo VietNam: a study of cross cultural communication = Chiến lược sử dụng ngôn từ và phi ngôn từ trong tiếp thị của PepsiCo Việt Nam: một nghiên cứu giao tiếp giao văn hóa - Phạm, Thị Vân Anh (2020)
PepsiCo is one of the leading companies in the soft drinks, snacks and food marketplace. As considered as the corporation which has the most successful and suitable strategies, PepsiCo is the object of a lot of research. However, they just have been focusing on economics fields and business. Therefore, this is the first project which study on marketing strategy of PepsiCo interm of the Cross Cultural Communication through verbal and nonverbal cues used by the Corporation. The paper begins by reviewing the current literature on Marketing, Verbal and non-verbal cues, and related studies. The investigation then analyzing and defining the specific verbal or non-verbal cues used by PepsiCo. This study also involved the participation of consumers of two generation – the young and the old, who have used this products and see it every day. The feelings of the consumers about the products demonstrate how much the cues are understood and how they work. The results of the study indicate that 1) Marketing strategies built based on non-verbal cues which are price, image, and endorsements are much more effective in Vietnamses market; 2) Cultural factors should be considered first by producers because of such great affection in controlling consumers buying behavior. Based on those research results, the researcher gave some recommendations for marketing strategies of PepsiCo Vietnam in particular and other beverage brands in Vietnam’s market in general – where they should focus on and what can be neglected to minimum Culture shock and maximum profits.